Clustered multidrug‐resistant Bordetella petrii in adult cystic fibrosis patients in Ireland: case report and review of antimicrobial therapies. Issue 1 (March 2014) - Carleton, Ailise; Casserly, Brian; Power, Lorraine; Linnane, Barry; O'flaherty, Grainne; Powell, James; Hartnett, Peig; Collins, Jonathan; Murphy, Philip; Kenna, Dervla; O'connell, Nuala H.; Dunne, Colum
Abstract : Abbreviations: bd, twice day −1 ; i.v., intravenously; MRSA, meticillin‐resistant Staphylococcus aureus ; MSSA, meticillin‐sensitive S. aureus ; od, once day −1 ; p.o., by mouth; tds, three times day −1 Introduction: Bordetella petrii is an emerging pathogen. Whilst association with cystic fibrosis (CF) has been described previously, this is the first report to our knowledge of multidrug‐resistant B. petrii incidence in an Irish CF patient population. Case presentation: Using a case series of four adult CF patients with varying baselines of health, one of whom was asymptomatic, this report attempts correlation of B. petrii colonization, by one common strain, with incidence of acute exacerbation of symptoms. As definitive guidelines for antimicrobial sensitivity/resistance do not exist for B. petrii, we completed a systematic review of available literature to collate evidence of antimicrobial efficacy against B. petrii. Comparison with the isolates in this study indicated B. petrii sensitivity to piperacillin/tazobactam and minocycline but resistance to antimicrobials in the macrolide, other β‐lactam and fluoroquinolone groups. Conclusion: To our knowledge, this is the first report of multiple CF patients sharing a strain of B. petrii . Furthermore, B. petrii may be under‐identified in CF patients and should be considered when evaluating exacerbation of CF symptoms.